2019
DOI: 10.1167/iovs.19-28023
|View full text |Cite
|
Sign up to set email alerts
|

Vision Parameters Most Important to Functionality in Glaucoma

Abstract: PurposeTo determine the importance of various vision parameters to functionality in glaucoma.MethodsVision was measured using seven parameters: visual acuity (VA), contrast sensitivity (CS), integrated visual field (IVF), area under the log CS function (AULCSF), color vision, stereoacuity, and VA with noise (ViN). Likelihood ratio testing (LRT) determined if the full set of visual parameters significantly explained variability in 10 functional outcomes. For outcomes where the visual contribution was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
1
21
0
2
Order By: Relevance
“…Many parameters subserved by BCs and HCs are altered in glaucoma, consistent with functional deficits in outer retina. 19 24 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many parameters subserved by BCs and HCs are altered in glaucoma, consistent with functional deficits in outer retina. 19 24 …”
mentioning
confidence: 99%
“…Many parameters subserved by BCs and HCs are altered in glaucoma, consistent with functional deficits in outer retina. [19][20][21][22][23][24] Structural changes localized to the outer retina are temporally correlated with inner retinal pathology in glaucoma patients and therefore appear dependent on the state of disease progression. 8,25 However, it is unclear whether these abnormalities result directly from glaucomatous insult or are a secondary consequence of inner retina damage.…”
mentioning
confidence: 99%
“…One potential limitation of this study is its use of self-reported measures of sensory function; however, this may also be viewed as a strength, as measuring vision using a single objective measure may not capture the full dimensionality of the effect of vision on function. 38 Another limitation is the older age of the population and the fact that a majority of participants walked slowly at baseline; future studies should examine the association between sensory function and walking speed in a younger cohort, where a difference in the rate of decline of walking speed by sensory function may be more apparent.…”
Section: Discussionmentioning
confidence: 99%
“…O glaucoma vai progressivamente reduzindo o campo visual o que acarreta mais dificuldade para enxergar os objetos com clareza, limitando a realização das AVDs, como se alimentar, se vestir, ler, escrever e até tomar banho 5,7,11,19,23 . A falta de autonomia aumenta com o avanço da severidade da doença, de modo que quanto maior deficiência visual, mais dependência de outras pessoas, afetando as relações sociais de pacientes glaucomatosos 24,25 .…”
Section: Discussionunclassified
“…O domínio do meio ambiente é afetado principalmente na habilidade de transporte. A capacidade de dirigir é afetada pela dificuldade de adaptação à diferentes luminosidades,em especial no período da noite pelo prejuízo na visão noturna e em dias nublados 2,15,19,24,26 .…”
Section: Discussionunclassified